Symbiotic Performance of Diverse Frankia Strains on Salt-Stressed Casuarina glauca and Casuarina equisetifolia Plants - Ngom, Mariama; Gray, Krystelle; Diagne, Nathalie; Oshone, Rediet; Fardoux, Joel; Gherbi, Hassen; Hocher, Valérie; Svistoonoff, Sergio; Laplaze, Laurent; Tisa, Louis S.; Sy, Mame O.; Champion, Antony (Frontiers in Plant Science, 2016)
Symbiotic nitrogen-fixing associations between Casuarina trees and the actinobacteria Frankia are widely used in agroforestry in particular for salinized land reclamation. The aim of this study was to analyze the effects of salinity on the establishment of the actinorhizal symbiosis between C. glauca and two contrasting Frankia strains (salt sensitive; CcI3 vs. salt tolerant; CeD) and the role of these isolates in the salt tolerance of C. glauca and C. equisetifolia plants. We show that the number of root nodules decreased with increasing salinity levels in both plants inoculated with CcI3 and CeD. Nodule formation did not occur in seedlings inoculated with CcI3 and CeD, at NaCl concentrations above 100 and 200 mM, respectively. Salinity also affected the early deformation of plant root hairs and reduced their number and size. In addition, expression of symbiotic marker Cg12 gene, which codes for a subtilase, was reduced at 50 mM NaCl. These data suggest that the reduction of nodulation in C. glauca under salt stress is in part due to inhibition of early mechanisms of infection. We also show that prior inoculation of C. glauca and C. equisetifolia with Frankia strains CcI3 and CeD significantly improved plant height, dry biomass, chlorophyll and proline contents at all levels of salinity tested, depending on the Casuarina-Frankia association. There was no correlation between in vitro salt tolerance of Frankia strains and efficiency in planta under salt-stressed conditions. Our results strongly indicate that increased N nutrition, photosynthesis potential and proline accumulation are important factors responsible for salt tolerance of nodulated C. glauca and C. equisetifolia.